Ethical and legal considerations in the relationship between medical scheme and member - Snoyman, Howard (My University, 2012)
South African medical schemes (health insurance or medical aid) companies offer insurance to the general public in the form of a multitude of different schemes. Each scheme has its own unique range of benefits, but certain exclusions apply across the board in respect of all schemes operated by a medical aid. In this research report, I investigate the rationale and necessity, as well as some of the ethical and legal implications of numerous notable exclusions. I further make relevant recommendations with respect to their application within the legal and ethical framework of the South Africa’s Consumer Protection Act, No. 68 of 2010.
Keywords: Bioethics; Health Care Costs